Unveiling hidden active nuclei in MaNGA star-forming galaxies with He ii λ4686 line emission - Tozzi, Giulia; Maiolino, Roberto; Cresci, Giovanni; Piotrowska, Joanna M; Belfiore, Francesco; Curti, Mirko; Mannucci, Filippo; Marconi, Alessandro (Monthly notices of the Royal Astronomical Society, 2023)
ABSTRACT Nebular He ii λ4686 Å line emission is useful to unveil active galactic nuclei (AGN) residing in actively star-forming (SF) galaxies, typically missed by the standard BPT classification. Here, we adopt the He ii diagnostic to identify hidden AGN in the Local Universe using for the first time spatially resolved data from the Data Release 15 of the Mapping Nearby Galaxies at APO survey (MaNGA DR15). By combining results from He ii and BPT diagnostics, we overall select 459 AGN host candidates (∼10 per cent in MaNGA DR15), out of which 27 are identified as AGN by the He ii diagram only. The He ii-only AGN population is hosted by massive (M* ≳ 1010 M⊙) SF Main Sequence galaxies and on average less luminous than the BPT-selected AGN. Given the He ii line faintness, we revisit our census accounting for incompleteness effects due to the He ii sensitivity limit of MaNGA. We thus obtain an overall increased fraction (11 per cent) of AGN in MaNGA compared to the BPT-only census (9 per cent), which further increases to 14 per cent for galaxies more massive than 1010 M⊙; interestingly, on the SF Main Sequence the increase is by about a factor of 2. A substantial number of AGN in SF galaxies points to significant, coeval star formation and black hole accretion, consistently with results from hydrodynamical simulations and with important implications on quenching scenarios. In view of exploring unprecedented high redshifts with JWST and new ground-based facilities, revisiting the standard BPT classification through novel emission-line diagnostics is fundamental to discover AGN in highly SF environments.